The Effect of Social Capital Dimension on Lecture Performance - Hartini, Hartini; Sapinah, Sapinah; N, Kristanty Marina Natalia; Wardhana, Aditya; Rahmawati, Rahmawati (JURNAL AL-TANZIM, 2023)
This study aims to determine and analyze the effect of structures, rational and cognitive dimensions of social capital on lecturers’ performance. It employs a quantitative approach to research within the ex post facto design. The sample of the study was 67 respondents from Patompo University. Data were collected using questionnaires and documentations. Data analysis was carried out through analytical activities, which includes prerequisite test analysis and hypothesis testing. The results of the study show that: 1) overall, structural dimension of social capital, rational dimension of social capital, and cognitive dimension of social capital have a positive and significant effect on the lecturer performance; 2) structural dimension of social capital have a positive and significant effect on the lecturer performance; 3) rational dimension of social capital have a positive and significant effect on the lecturer performance; and 4) cognitive dimension of social capital have a positive and significant effect on the lecturer performance. This finding becomes an input for higher education leaders to better understand and provide with insights into which social dimension can affect the performance of lecturers by considering school backgrounds, increasing the lecturer participation thorugh reward system and appropriate performance evaluation models.